Kontrol Topografi Terhadap Distribusi Ketebalan dan Pengayaan Nikel Laterit Desa Torete Morowali - Aulya Tiara Putri; Muh Kasim; Ninasafitri Ninasafitri (-, 2026)
This study aims to analyze the influence of slope gradient on the distribution of laterite profile thickness and nickel (Ni) grade in Bungku Pesisir District, Morowali. The research methods include surface geological mapping, petrographic analysis, and geochemical analysis using X-Ray Fluorescence (XRF). The results indicate that slope gradient is the primary controlling factor in the lateritization process. Gentle slopes tend to have thicker laterite profiles, reaching up to 31.2 m at TRT-19, whereas steeper slopes show significantly thinner profiles, approximately 10 m at TRT-35. In addition to morphometric factors, the presence of rock fractures enhances water infiltration, which in turn intensifies the leaching of chemical elements. The distribution of Ni grade reaches its maximum in the saprolite zone due to supergene enrichment processes controlled by groundwater mobility. It is concluded that the interaction between slope morphology and rock structure plays a significant role in controlling the distribution and quality of lateritic nickel deposits in the study area.